The spatial pattern and influencing factors of tourism eco-efficiency in Inner Mongolia, China - Wang, Yuewei; Wu, Xinyang (Frontiers in Public Health, 2022)
Tourism eco-efficiency is the performance basis for evaluating green total factor productivity and sustainable development. The objective of this study was to measure the tourism eco-efficiency in Inner Mongolia and explore its influencing factors. The aim was to provide accurate reference for improving the quality and efficiency of tourism in Inner Mongolia and promoting the sustainable development of regional economy and society. The tourism eco-efficiency in Inner Mongolia from 2009 to 2019 was calculated using the super-slacks based measure model with undesirable output. The spatial variation function was used to explore the spatial evolution pattern of tourism eco-efficiency in Inner Mongolia, and the influencing factors of the spatial evolution were analyzed by geographic weighted regression. Tourism eco-efficiency in Inner Mongolia is relatively low. The eco-efficiency values among the cities in Inner Mongolia vary, and their distribution is not balanced. The structural of tourism eco-efficiency in Inner Mongolia have been consistent from 2009 to 2019. The degree of homogenization in the overall direction is relatively good. Furthermore, its spatial distribution form and internal structure evolution show certain regularity and continuity. The pattern evolution of tourism eco-efficiency in Inner Mongolia is jointly driven by economic level, environmental regulation, industrial structure, traffic condition, resource endowment and tourism reception facilities. The influencing factors show obvious spatial heterogeneity. From the perspective of Inner Mongolia, the difference of tourism eco-efficiency value from 2009 to 2019 is relatively large, but the number of effective areas in the efficiency frontier generally showed a fluctuating growth trend. The range parameters of tourism eco-efficiency showed a decreasing trend, and the spatial correlation effect of tourism eco-efficiency in Inner Mongolia showed a decreasing trend under the influence of structural spatial differentiation.